Analysis of Mobile Banking Usage and Other Factors on Banking Productivity in Indonesia Using the Malmquist Productivity Index (MPI) Approach - Yohana Marnala Marpaung; Fajra Octrina (DINASTI RESEARCH, 2024)
This study analyzes the impact of fintech technology on the productivity and efficiency of traditional banks in Indonesia that provide mobile banking services. While fintech has improved financial transactions and operational efficiency, previous research shows mixed results regarding the effect of fintech on bank productivity. This study fills the research gap by analyzing how fintech integration affects the efficiency of traditional banks using recent data. Using the Malmquist Productivity Index (MPI), this study evaluates the efficiency of nine traditional banks in Indonesia based on annual report data. The variables analyzed include Mobile Transaction Market Share (PH), Gross Domestic Product (GDP), Non-Performing Loan Ratio (NPL), Capital Ratio (CAP), Total Assets (A), and M2 Exchange Rate (MS). The descriptive analysis results show that the variables of NPL, CAP, and total assets have no significant impact on productivity. However, GDP and M2 have a strong influence on improving bank efficiency through fintech technology. This study concludes that fintech is important to improve banking efficiency in Indonesia and banks should prioritize technological innovation to boost productivity. Further research is needed to explore additional variables in this relationship.